Strategi Inovatif untuk Meningkatkan Budaya Literasi dengan Model Pembelajaran Kooperatif Tipe TGT dan Media Ular Tangga pada Materi Perubahan Masyarakat Masa Islam di SMP Muhammadiyah 2 Taman Sidoarjo - Maryati, Nofi; Saputra, Bachtiar Adi (TSAQOFAH, 2024)
This article explores the use of innovative strategies in improving literacy culture among class 8B students at SMP Muhammadiyah 2 Taman Sidoarjo. The main focus of this research is to apply the TGT (Teams-Games-Tournaments) type cooperative learning model combined with the snakes and ladders game media in learning material about changes in Islamic society. Involving aspects of geography, economics, social and culture, this approach aims to stimulate interest in reading, increase understanding and build students' literacy skills. The research method applied in this research carries a combinative approach between the TGT (Teams-Games-Tournaments) type cooperative learning model and the snakes and ladders game media. The results of observations carried out showed a significant increase in students' active participation during the learning process. Students are more actively involved in group discussions, questions, and given assignments. They are not only recipients of information, but also main actors in their own learning. This increase in participation indicates that TGT's cooperative approach and the snakes and ladders game media are able to create a learning environment that stimulates more intensive student involvement. Evaluation of the impact of this innovative strategy in more detail is measured through assessment tests. Positive results on the test show that the TGT cooperative approach and the snakes and ladders game media have a real impact on students' academic achievement. The conclusion we can draw is that this innovative strategy proves that the use of the TGT cooperative learning model with the snakes and ladders game media can be an effective step in improving literacy culture among students.